Extension training for banana value addition among smallholder farmers in Meru and Tharaka-Nithi counties, Kenya - Kirimi, Florence K.; Nyambane, Charles O.; Njeru, Lucy K.; Mogaka, Hezron R. (Academic Journals, 2021)
Extension training is intended to increase the efficiency and performance of the human resource that acts responsibly in a society based on a communication interaction with knowledge sources. The main objective of this study was to assess the effect of training farmers on banana value addition among smallholder farmers in Meru and Tharaka-Nithi counties. The study adopted a pragmatic paradigm and a cross-sectional survey design and sampled 370 and 30 farmers proportionately obtained from 269,499 and 19,303 smallholder banana farmers in Meru and Tharaka-Nithi counties, respectively. Structured and semi-structured questionnaires were used to collect primary data from the respondents. Secondary data were obtained from official extension and production records in the two counties as well as related literature. Data was analysed using descriptive statistics to determine frequencies, percentages and means. Regression analysis was conducted to examine relationships between the study variables. The results revealed that there was an association between training farmers on the various method of banana value addition and adoption of selected banana value addition technologies was statistically significant at 1% level of significance (p-value = 0.000<0.01,  =156.391, df 1). The study concludes that farmers having a preferred facilitator in training positively influenced the adoption of banana value addition technologies. The study recommends the government should create and implement policies such as collaborating with high learning institution like universities and set days where they will be training farmers on various methods of banana value addition.
Keywords: Extension training; banana value addition; small holder farmers